2006
DOI: 10.1111/j.1532-7795.2006.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

The Peer Context of Adolescent Substance Use: Findings from Social Network Analysis

Abstract: To examine the peer context of adolescent substance use, social network analysis was used to measure three domains of attributes of peer networks: social embeddedness, social status, and social proximity to substance users. The sample was a panel of 5,104 sixth, seventh, and eighth graders in three public school systems surveyed every 6 months for five assessments. Hierarchical generalized linear models showed that adolescents less embedded in the network, with greater status, and with closer social proximity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
364
2
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(415 citation statements)
references
References 39 publications
36
364
2
13
Order By: Relevance
“…Each of these indicators of positive peer relations may have a unique link with externalizing behavior. For instance, Ennett et al (2006) showed that popularity, dyadic friendships, and proximity each uniquely predicted adolescents' substance use. In the present study, we therefore focus on these three aspects of children's positive peer relations by studying whether each is uniquely associated with children's externalizing behavior.…”
Section: Different Aspects Of Positive Peer Relationsmentioning
confidence: 99%
“…Each of these indicators of positive peer relations may have a unique link with externalizing behavior. For instance, Ennett et al (2006) showed that popularity, dyadic friendships, and proximity each uniquely predicted adolescents' substance use. In the present study, we therefore focus on these three aspects of children's positive peer relations by studying whether each is uniquely associated with children's externalizing behavior.…”
Section: Different Aspects Of Positive Peer Relationsmentioning
confidence: 99%
“…It is now well acknowledged that adolescents tend to adopt health behaviours that are similar to their friends' behaviours, and this has been shown in a range of domains such as substance use, nutrition, and sexual activity (Ajilore, 2015;Clark & Loheac, 2007;Ennett et al, 2006;Kobus, 2003;McGloin et al, 2014;Simons-Morton & Farhat, 2010; T. W. Valente et al, 2004). Moreover, exposure to substance use is associated with the structural position of an adolescent in the network.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exposure to substance use is associated with the structural position of an adolescent in the network. Studies suggest that those with more friendships are more likely to smoke or to drink than those with fewer friends (Balsa et al, 2011;Ennett et al, 2006;Fujimoto & Valente, 2012;Huang et al, 2014;Mundt, 2011;Osgood et al, 2014;Tucker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Peer standing also has been addressed using indicators derived from social network analysis, with an increasing number of studies that assess both peer standing and substance use among adolescents using this framework (e.g., Alexander et al, 2001;Ennett & Baumann, 1993;Ennett et al, 2006;Pearson & West, 2003;Rodkin et al, 2000;Valente et al, 2005). According to social network theory (Knoke & Kulinski, 1982;Wasserman & Faust, 1994), individuals central to a bounded network (such as a classroom or grade) are both relatively visible and well-connected to others in the network, whereas less central or marginal (peripheral) members of the network are relatively less visible and less well-connected.…”
Section: Introductionmentioning
confidence: 99%
“…For example, among children in grades 6 through 8, those who receive relatively high numbers of "friend" or "liking" nominations, including popular children (higher numbers of "friend" nominations; Valente et al, 2005) (2006) report that adolescents who are "liked but not too well-liked"-a classification perhaps most closely consistent with "average" sociometric status-are least likely to be smokers. The relative status of adolescent friends also impacts the extent to which adoption of drinking behavior occurs over time: young adolescents are more likely to adopt the drinking behavior of a unilateral friend with higher status (Bot et al, 2001), and are more susceptible to influence from well-liked others (Latane, 1981), affirming the power of elevated peer standing to influence substance use behaviors.Peer standing also has been addressed using indicators derived from social network analysis, with an increasing number of studies that assess both peer standing and substance use among adolescents using this framework (e.g., Alexander et al, 2001;Ennett & Baumann, 1993;Ennett et al, 2006;Pearson & West, 2003;Rodkin et al, 2000;Valente et al, 2005). According to social network theory (Knoke & Kulinski, 1982;Wasserman & Faust, 1994), individuals central to a bounded network (such as a classroom or grade) are both relatively visible and well-connected to others in the network, whereas less central or marginal (peripheral) members of the network are relatively less visible and less well-connected.…”
mentioning
confidence: 99%